Overexpression of Thioredoxin-1 Blocks Morphine-Induced Conditioned Place Preference Through Regulating the Interaction of γ-Aminobutyric Acid and Dopamine Systems - Li, Xiang; Huang, Mengbing; Yang, Lihua; Guo, Ningning; Yang, Xiaoyan; Zhang, Zhimin; Bai, Ming; Ge, Lu; Zhou, Xiaoshuang; Li, Ye; Bai, Jie (Frontiers in Neurology, 2018)
Morphine is one kind of opioid, which is currently the most effective widely utilized pain relieving pharmaceutical. Long-term administration of morphine leads to dependence and addiction. Thioredoxin-1 (Trx-1) is an important redox regulating protein and works as a neurotrophic cofactor. Our previous study showed that geranylgeranylaceton, an inducer of Trx-1 protected mice from rewarding effect induced by morphine. However, whether overexpression of Trx-1 can block morphine-induced conditioned place preference (CPP) in mice is still unknown. In this study, we first examined whether overexpression of Trx-1 affects the CPP after morphine training, and further examined the dopamine (DA) and γ-aminobutyric acid (GABA) systems involved in rewarding effect. Our results showed that morphine-induced CPP was blocked in Trx-1 overexpression transgenic (TG) mice. Trx-1 expression was induced by morphine in the ventral tegmental area (VTA) and nucleus accumbens (NAc) in wild-type (WT) mice, which was not induced in Trx-1 TG mice. The DA level and expressions of TH and D1 were induced by morphine in WT mice, which were not induced in Trx-1 TG mice. The GABA level and expression of GABABR were decreased by morphine, which were restored in Trx-1 TG mice. Therefore, Trx-1 may play a role in blocking CPP induced by morphine through regulating the expressions of D1, TH, and GABABR in the VTA and NAc.